2021
DOI: 10.55230/mabjournal.v50i1.1502
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR CHARACTERIZATION AND MATING STUDY OF Fusarium proliferatum FROM VARIOUS HOSTS IN MALAYSIA

Abstract: Fusarium proliferatum is a well-known plant pathogenic fungus-infected many crops. The present study was carried out to molecularly identified and characterized morphologically identified F. proliferatum from various hosts and substrates. The species identity of the isolates was verified as F. proliferatum based on TEF-1α sequences and phylogenetic analysis indicated high intraspecific variations. RFLP-IGS analysis also indicated high intraspecific variations of which the isolates were clustered into three RFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Molecular identification and phylogenetic analysis based on the translation elongation factor 1-alpha (TEF-1α) sequences, along with mating studies on multiple isolates from diverse hosts and locations, have suggested that there is no relation between F. proliferatum isolates and their hosts or geographic origins [18,37,55,56]. Nevertheless, an evaluation of vegetative compatibility among isolates of F. proliferatum indicated that isolates recovered from maize, onion, sugarcane, and rice could be classified into different vegetative compatibility groups (VCGs), indicating a correlation between VCGs and host preferences [12].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular identification and phylogenetic analysis based on the translation elongation factor 1-alpha (TEF-1α) sequences, along with mating studies on multiple isolates from diverse hosts and locations, have suggested that there is no relation between F. proliferatum isolates and their hosts or geographic origins [18,37,55,56]. Nevertheless, an evaluation of vegetative compatibility among isolates of F. proliferatum indicated that isolates recovered from maize, onion, sugarcane, and rice could be classified into different vegetative compatibility groups (VCGs), indicating a correlation between VCGs and host preferences [12].…”
Section: Discussionmentioning
confidence: 99%